Competitiveness Analysis and Strategies to Improve Small and Medium Enterprises Performance - Wafa A.F, Muhamad; Waridin, Waridin; Tantra, I Gusti Lanang Putu (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
Global economic dynamics encourage industry to excel and be competitive. This research aims to identify industry characteristics, measure the level of industrial competitiveness; and then provide strategy suggestions to increase industrial competitiveness. The Porter Diamond Model is used in this research to measure the level of competitiveness of the exhaust industry, where there are four indicators of industrial competitiveness, namely factor conditions, demand conditions, company strategy and competitive structure, as well as related and supporting industries. Using qualitative methods, data collection is carried out using questionnaires. The primary data used was taken from exhaust manufacturers in Purbalingga Regency totaling 67 respondents. Strategy recommendations for increasing industrial competitiveness are determined based on urgency-performance analysis. The results of the industrial competitiveness analysis show that condition factors provide the highest contribution to the competitiveness of the exhaust industry compared to other indicators. Urgency-performance analysis shows that 5 out of 10 sub-factors driving competitiveness have underact status. The strategy to increase industrial competitiveness focuses on competitiveness sub-factors with â€œunder actâ€ status. These strategies include: 1) Providing better business development systems and services, 2) Developing business capacity, and 3) Expanding industrial cooperation.